Analysis of Population Administration Service Policy in Palembang City - Verronica Pradaneisyah; Muhammad Nur Budiyanto; Raniasa Putra (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze population administration service policies in Palembang City through a monitoring and evaluation approach, focusing on shifting functions and obstacles faced in their implementation. Population administration is a very important basic service for the community, which includes the recording of personal data such as birth certificates, family cards, and ID cards, as the main foundation in various aspects of citizens' lives. The quality of this service reflects good and accountable governance, where the Population and Civil Registration Office (Disdukcapil) plays a central role in ensuring the effectiveness and transparency of services. In this context, public policy monitoring and evaluation are essential instruments to identify various operational constraints and design improvement solutions, as well as to assess the extent to which the shift in service functions towards digitalization and other innovations can be optimally accommodated. The research method used is qualitative with a case study approach, analyzing policy implementation, the role of actors, success indicators, and their impact on service quality and public trust levels. The results of the study show that, although various technological innovations have been implemented, such as online systems and the use of digital devices, obstacles such as limited internet access, low digital literacy, and coordination challenges between agencies are still the main obstacles in accelerating the shift in service functions. This study recommends strategies for increasing human resource capacity, strengthening technological infrastructure, and continuous monitoring and evaluation so that policy implementation can run more effectively, equitable, and responsive to community needs. Thus, it is hoped that population administration services in Palembang City can further increase public satisfaction, trust, and support more efficient and accountable governance.